If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 21 = 9x + -63 Reorder the terms: 21 + 2x = 9x + -63 Reorder the terms: 21 + 2x = -63 + 9x Solving 21 + 2x = -63 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 21 + 2x + -9x = -63 + 9x + -9x Combine like terms: 2x + -9x = -7x 21 + -7x = -63 + 9x + -9x Combine like terms: 9x + -9x = 0 21 + -7x = -63 + 0 21 + -7x = -63 Add '-21' to each side of the equation. 21 + -21 + -7x = -63 + -21 Combine like terms: 21 + -21 = 0 0 + -7x = -63 + -21 -7x = -63 + -21 Combine like terms: -63 + -21 = -84 -7x = -84 Divide each side by '-7'. x = 12 Simplifying x = 12
| 6x+55=2x+27 | | 3(4x+5)=17x+12-5x+3 | | 6x+35+9x=15(x+2)-25 | | y+34=19 | | 3-9x=84 | | 5y+12-5=22 | | 2(-x+8)=24 | | 2x^2+162=0 | | 6(x+2)=2(3x+8)-4 | | 3x+4-5x-14=10 | | 7d-4d-4d-6=2d | | 11x+2=14x-10 | | 10y=40x+3xy | | 2(t-2)=6 | | 7x-y=(x) | | 0.5(x+2)-(3x+8)=1.6(x-2)+9 | | 3(7x+20Y)+7(-3x+6y)= | | y-37=-67 | | -21=n-10 | | 2(2x+5)=40 | | 3(x-5)=2(x+1)+x | | 5+9x=-13 | | -5.7-44.2=-8.3v | | -7y+3=8y+1 | | 3(7x+20Y)7(-3x+6y)= | | 4x+8-3x-10=-33 | | -6-2x-1=4x+8-6x-3 | | 2(n+5)=11 | | 7=-11+3(6+5) | | 2(n+5)=111 | | -5r-r=5r-8 | | 3x+5x+4x-2=10 |